2011
DOI: 10.1176/appi.neuropsych.23.3.316
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Dementia Predicts Worse Neuropsychological Functioning Among HIV-Infected Persons

Abstract: HIV-negative individuals with a family history of dementia (FHD) are more likely to develop dementia than those without a FHD. Whether FHD increases risk for neuropsychological (NP) impairment in HIV+ persons is unknown. As part of a multi-site study into HIV-Associated Neurocognitive Disorders (HAND), we captured FHD with a free-response, self-report question, and assessed NP performance with a comprehensive battery of tests. We examined HIV+ persons with (n=190) and without (n=916) self-reported FHD. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Details of the neuropsychological battery along with normative sources are presented in the Appendix. The classification of these particular tests into specific domains was theoretically, rather than empirically derived (e.g., factor analysis), to maintain consistency with previous studies that have successfully used these categorizations to detect HIV-related deficits with acceptable sensitivity (Antinori et al, 2007; Byrd et al, 2011; Carey et al, 2004; Cherner et al, 2010; Devlin et al, 2012; Fellows et al, 2012; Heaton et al, 2010, 1995; Heaton, 2011; Moore et al, 2011; Rippeth et al, 2004; Ryan et al, 2005; Woods et al, 2004). All assessments were administered by trained staff and reviewed by a clinical neuropsychologist for quality assurance.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the neuropsychological battery along with normative sources are presented in the Appendix. The classification of these particular tests into specific domains was theoretically, rather than empirically derived (e.g., factor analysis), to maintain consistency with previous studies that have successfully used these categorizations to detect HIV-related deficits with acceptable sensitivity (Antinori et al, 2007; Byrd et al, 2011; Carey et al, 2004; Cherner et al, 2010; Devlin et al, 2012; Fellows et al, 2012; Heaton et al, 2010, 1995; Heaton, 2011; Moore et al, 2011; Rippeth et al, 2004; Ryan et al, 2005; Woods et al, 2004). All assessments were administered by trained staff and reviewed by a clinical neuropsychologist for quality assurance.…”
Section: Methodsmentioning
confidence: 99%
“…All told, impaired executive functions are detected in approximately 50% of HIV+ individuals with neurocognitive impairment (Heaton et al, 2011). Executive dysfunction can emerge early in the course of infection (Moore et al, 2011), and the severity of impairment tends to increase with advancing HIV disease (Reger et al, 2002). Although there is no single prototypical pattern of neurocognitive impairment in HIV, it has been argued that executive dysfunction may be a cardinal feature of HAND in the cART era (Dawes et al, 2008).…”
mentioning
confidence: 99%
“…This is in contrast to studies that have shown that abnormal biomarker concentrations (particularly Aβ-42) are more likely in patients who have a family history of AD particularly via maternal inheritance [39]. While future research should determine FHD in a more objective format, perhaps via confirmation with clinicians of family members, this study and others [24] provide support for the use of self-report FHD as an easy to gather and inexpensive proxy for familial risk/genotype for dementia.…”
Section: Discussionmentioning
confidence: 60%
“…When participants were unable to provide all of this information, they were coded as not having FHD to avoid overestimation. Participants who were adopted and could not provide information about their family history were excluded [24]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation